2001
DOI: 10.1101/lm.36801
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Memory Formation Is Enhanced across Sleep Intervals with High Amounts of Rapid Eye Movement Sleep

Abstract: Recent studies indicated a selective activation during rapid eye movement (REM) sleep of the amygdala known to play a decisive role in the processing of emotional stimuli. This study compared memory retention of emotional versus neutral text material over intervals covering either early sleep known to be dominated by nonREM slow wave sleep (SWS) or late sleep, in which REM sleep is dominant. Two groups of men were tested across 3-h periods of early and late sleep (sleep group) or corresponding retention interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
387
12
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(436 citation statements)
references
References 60 publications
18
387
12
6
Order By: Relevance
“…Importantly, the two groups did not differ in their recognition performance for neutral images. This emotion-specific effect of REM sleep corroborates earlier work which found that three hours of late night REM dominant sleep facilitates the consolidation of negative images (Groch, Zinke, Wilhelm, & Born, 2015) and information within negative stories (Wagner, Gais, & Born, 2001), relative to three hours of sleep obtained in the first half of the night where REM sleep is less abundant. Correlational analyses have yielded similar results, finding that the amount of time spent in REM sleep across a 12-hour retention interval correlates positively with recall performance for negative but not neutral objects within complex images (Payne et al, 2012).…”
Section: The Role Of Rem Sleep and Amygdala Function In Emotional Memorysupporting
confidence: 89%
See 2 more Smart Citations
“…Importantly, the two groups did not differ in their recognition performance for neutral images. This emotion-specific effect of REM sleep corroborates earlier work which found that three hours of late night REM dominant sleep facilitates the consolidation of negative images (Groch, Zinke, Wilhelm, & Born, 2015) and information within negative stories (Wagner, Gais, & Born, 2001), relative to three hours of sleep obtained in the first half of the night where REM sleep is less abundant. Correlational analyses have yielded similar results, finding that the amount of time spent in REM sleep across a 12-hour retention interval correlates positively with recall performance for negative but not neutral objects within complex images (Payne et al, 2012).…”
Section: The Role Of Rem Sleep and Amygdala Function In Emotional Memorysupporting
confidence: 89%
“…Research which demonstrates that many compounds with antidepressant properties suppress REM sleep (Mayers & Baldwin, 2005;Steiger & Kimura, 2010; also see: Murck et al, 2003;Nofzinger et al, 1995;Sonntag et al, 1996), considered alongside evidence that REM sleep duration and density is associated with the consolidation of negative memories (Gilson et al, 2015;Groch et al, 2015;Nishida et al, 2009;Payne et al, 2012;Wagner et al, 2001;Wiesner et al, 2015), has led researchers to speculate that REM sleep alterations may underlie the emotional memory bias observed in depressed patients (Walker & van der Helm, 2009;Walker, 2009). However, the majority of studies directly investigating the effect of REM sleep on emotional memory consolidation focus exclusively on comparisons between recognition performance for neutral and negatively salient stimuli (however see : Cairney, Durrant, Power, & Lewis, 2015), ignoring the possibility that REM sleep may also play a role in the consolidation of positive memories.…”
Section: The 'Affect Tagging and Consolidation' (Atac) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation in these regions suggest that memory consolidation processes, in particular emotional memories, may occur during REM sleep (Hu, Stylos-Allan, & Walker, 2006;Nishida, Pearsall, Buckner, & Walker, 2009;Sterpenich et al, 2009;Wagner, Gais, & Born, 2001;Wagner, Hallschmid, Rasch, & Born, 2006;Walker, 2009). While a large body of data support the involvement of sleep in memory (for review, see Dang-Vu, Desseilles, Peigneux, & Maquet, 2006), the relationship between processes related to memory consolidation and those underlying dream experience is still poorly understood (e.g.…”
Section: Distribution Of Brain Activity During Rem Sleepmentioning
confidence: 99%
“…There is now abundant evidence that the amygdala specializes in processing of emotion, particularly negative emotions, and functions as the "decisional" or "appraisal organ" of the mind (Bechara et al 1999;Davidson and Irwin 1999;LeDoux 1996). In addition, along with hippocampal sites, it apparently supports both emotional memory formation and reactivation of emotional memories during REM (Wagner et al 2001;Wilson and McNaughton 1994). It also contributes to regulation of other brain structures such as the hypothalamus that, in turn, regulate ongoing neuroendocrine processes in the developing organism (LeDoux 2002;Davis and Whalen 2001).…”
Section: Rem and Unconscious Appraisals Of Ecologic Context Via Activmentioning
confidence: 99%